Determinacion de los niveles de glicemia de los pobladores adultos de ambos sexos del sector II de Miguel Grau del distrito el Porvenir. julio - agosto 2010 - Mendocilla Dominguez, Leopoldo Rubén (2011)
This work was performed in order to determine blood glucose levels of the residents of sector II of Miguel Grau - The future. Included 64 adult men and women in a health talk about the issue, distributing information leaflets and encouraging them to be the glucose test, highlighting the importance of this in the diagnosis of diabetes. The blood sample was obtained fasting, we also applied a survey to collect personal data, vital signs, nutritional, socioeconomic, lifestyle and health. The quantitative determination of glucose in serum or plasma was by the enzymatic method, leading to read the sample to the spectrophotometer at 540 nm. The results obtained show that 90.63% of the populations have serum glucose levels within normal values and 6.25% has a marked hyperglycemia. Finally, the results were subjected to statistical hypothesis testing where it was found that there is a significant difference between people with hyperglycemia and those who remain normoglycemic, are likely to have diabetes by lifestyle